2008
DOI: 10.1038/ajh.2008.219
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Exposure and Angiogenic Factors in Pregnancy and Preeclampsia

Abstract: Cigarette smoking is associated with lower maternal sFlt-1 concentrations during pregnancy and preeclampsia. On the basis of these data, cigarette smoke exposure may decrease the risk of preeclampsia in part by moderating the anti-angiogenic phenotype observed in the syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
3
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 24 publications
2
65
3
5
Order By: Relevance
“…The mechanism leading to this outcome is currently unknown, but may include changes to maternal and placental angiogenic factors, endothelial function and immune responses, induced by cigarette smoking, all of which contribute to this disease pathology. In support of this, a recent study found an association between smoking in pregnancy and reduced levels of the angiogenic factor soluble FMS-like tyrosine kinase-1 in maternal circulation [41]. Further research is required to elucidate the organs effecting and affected by this change, and to identify whether these same pathways are conversely affected with asthma.…”
Section: Discussionmentioning
confidence: 58%
“…The mechanism leading to this outcome is currently unknown, but may include changes to maternal and placental angiogenic factors, endothelial function and immune responses, induced by cigarette smoking, all of which contribute to this disease pathology. In support of this, a recent study found an association between smoking in pregnancy and reduced levels of the angiogenic factor soluble FMS-like tyrosine kinase-1 in maternal circulation [41]. Further research is required to elucidate the organs effecting and affected by this change, and to identify whether these same pathways are conversely affected with asthma.…”
Section: Discussionmentioning
confidence: 58%
“…19,35 Cigarette smoking was previously shown to be associated with lower maternal sFlt-1 concentrations in uncomplicated pregnancy and pre-eclampsia. 45 In addition, overweight women with pre-eclampsia were demonstrated to have lower levels of sFlt-1 and higher levels of PlGF than pre-eclamptic women of normal weight. 46 Nevertheless, the narrow range of gestational age at blood collection, as well as the low number of smokers and pre-eclamptic patients of normal weight in this study, did not allow us to confirm these data.…”
Section: Discussionmentioning
confidence: 95%
“…18 Earlier studies indicate that cigarette smokers have lower circulating levels of sFlt1 than nontobacco users. 19,20 In vitro studies have reported that carbon monoxide, a major component in combustion, diminishes sFlt1 release from cultured endothelial cells, 21 whereas nicotine does not influence the production of sFlt1 from cultured placental cells. 22 Our findings of a lower risk of preeclampsia in cigarette smokers, who are exposed to carbon monoxide, but not in snuff users, who are only exposed to nicotine, are in agreement with these results.…”
Section: Wikström Et Al Effect Of Tobacco On Preeclampsiamentioning
confidence: 99%